Nonverbal Communication in Language Teaching: A Generic Perpective - Ahmed, BASHAR (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre), 2014)
تمت كتابة هذا المقال انطلاقا من القناعة التالية'' لم يستطلع التواصل غير الكلامي كفاية في أحسن الأحوال و تم تجاهله في أسوءها''. يعالج هذا المقال أيضا المظاهر العامة للقنوات المختلفة التي يستعملها الأساتذة بوعي أو بغيره. و يبقى الاهتمام و التركيز على التواصل غير الكلامي؛ الذي من الواضح أنه مهم أكثر مما يستوعبه الأساتذة. يختلجنا أمل هادئ أن نساهم في توعية الأساتذة بهذا الموضوع الجوهري. بدء على عود فإن هذه اللغة الصامتة هي الأكثر تعبيرا لكونها جزءا لا يتجزأ من الممارسات التعليمية. و عليه فإن مقارنة التواصل غير الكلامي بين الثقافتين الغربية و العربية يدخل حتما في نطاق هذا المقال.                                            The current paper evolves from a powerful claim that teachers’ nonverbal communication is underexplored at best and ignored at worst. It addresses generic aspects of the different channels that teachers utilize whether consciously or otherwise. However, the focus is on certain nonverbal communication aspects, which are clearly more substantial to the teaching-learning situation than we might suspect. We harbor a quiet hope that this paper raises teachers’ awareness toward these ubiquitous channels of messages. Again, to labor the point, this ‘‘silent language’’ is most outspoken as it is an indelible part of the teaching-learning practices. Besides, it is within the reach of this paper to juxtapose Western and Arab nonverbal communication for comparison and study.